2021
DOI: 10.1108/jrf-04-2020-0066
|View full text |Cite
|
Sign up to set email alerts
|

A volatility-match approach to measure performance: the case of socially responsible exchange traded funds (ETFs)

Abstract: PurposeThis study examines the risk-adjusted performance of socially responsible exchange traded funds (SR ETFs) in comparison to conventional ETFs.Design/methodology/approachThe main empirical result is based on a risk-adjusted performance metric that does not rely on a linear framework. It measures the difference between the returns of an ETF and the returns of a volatility-match and efficient portfolio. In addition, performance is measured using alpha based on single and multifactor formulations.FindingsRes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Conspicuously, the investment in the environment and clean energy indices have been growing exponentially due to the increasing interests of investors toward the clean environment, renewable energy sources, socially responsible initiatives and escalated threats to the global ecosystem (Naeem et al, 2021a;Karim, 2021a, b;. Green assets are earmarked with a green label which ensures that proceeds of these investments are attributed to the projects solely related to energy efficiency, material efficiency, clean and green transportation and recycling (Arif et al, 2021a;Lobato et al, 2021;Ferrat et al, 2022;Ielasi et al, 2018). Evidence suggests that environmental, social and governance stocks outperform the conventional financial markets (Broadstock et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conspicuously, the investment in the environment and clean energy indices have been growing exponentially due to the increasing interests of investors toward the clean environment, renewable energy sources, socially responsible initiatives and escalated threats to the global ecosystem (Naeem et al, 2021a;Karim, 2021a, b;. Green assets are earmarked with a green label which ensures that proceeds of these investments are attributed to the projects solely related to energy efficiency, material efficiency, clean and green transportation and recycling (Arif et al, 2021a;Lobato et al, 2021;Ferrat et al, 2022;Ielasi et al, 2018). Evidence suggests that environmental, social and governance stocks outperform the conventional financial markets (Broadstock et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Green assets are earmarked with a green label which ensures that proceeds of these investments are attributed to the projects solely related to energy efficiency, material efficiency, clean and green transportation and recycling (Arif et al. , 2021a; Lobato et al. , 2021; Ferrat et al , 2022; Ielasi et al.…”
Section: Introductionmentioning
confidence: 99%
“…This role of promoting energy innovation and market stability through financial means has also been confirmed in many scholars' studies (Kaiser and Welters, 2019;Naqvi et al, 2021;Taghizadeh-Hesary et al, 2021;Umar et al, 2021;Karim et al, 2022). The advantages of these financial instruments and the promotion of corporate social responsibility awareness (Ielasi et al, 2018;Ferrat et al, 2021;Lobato et al, 2021;Dorfleitner and Grebler, 2022), which can well match China's current development goals and become an important replacement and supplement of command-based environmental regulation policies (Ji et al, 2021).…”
Section: Literaturementioning
confidence: 79%
“…A group of scholars (e.g. Fang et al, 2022;Dorfleitner and Grebler, 2022;Yu et al, 2022;Lobato et al, 2021;Umar et al, 2021a, b, c, d;Kaiser and Welters, 2019;Lelasi et al, 2018) believe that green finance instruments can be considered a great opportunity to improve energy efficiency projects, while numerous previous studies have not found significant impacts of this type of financing on green projects. Cui et al (2020) conducted a multi-agent theory game and noticed the neutrality of green finance market.…”
Section: Literature Reviewmentioning
confidence: 99%